Floral, reproductive, and pollination biology of Floral, reproductive, and pollination biology of Eugenia myrcianthes Nied. - Guollo, Karina; Kosera Neto, Carlos; Rosa, Viviane da; Garay, Igor Alfonzo; Wagner Junior, Américo; Rocha, Matheus Araújo Moreira (Comunicata Scientiae, 2023)
Studies on species of the family Myrtaceae are mostly related to floristic surveys, reproduction involving large plant communities, and family taxonomy. Thus, the objective of this study was to elucidate aspects of the floral and reproductive biology, as well as floral visitors of ubajai (Eugenia myrcianthes Nied.). Studies were conducted on floral morphology and morphometry, identification of nectaries and structures attractive to floral visitors, characterization of floral visitors, stigma receptivity, and androecium maturation, pollen storage, in vitro viability testing, and characterization of the reproductive system. Ubajai flowers open at approximately 6:00 a.m., and their anthers are the main attractive structure to floral visitors. The main floral visitors and effective pollinators of ubajai are honeybees (Apis mellifera). The addition of 40% sucrose to the culture medium, using fresh pre-anthesis pollen, allows for a 90% germination rate. Ubajai pollen is recalcitrant, thus, it loses viability before 30 days of storage, even when stored in a refrigerator, freezer, liquid nitrogen, or natural environment. Ubajai can be considered a self-compatible plant; however, fertilization of flowers through cross-pollination also occurs, and apomixis does not occur.